(untitled) (Journal of Hama University, 2024)
The aim of this research is to study the grinding process using government mills and laboratory mill and its impact on the value of the starch damage and by using the SD MATIC and some of the measures obtained from the Mixolab device in addition to some physical and chemical lab., and all analyzes were done in the grain technology laboratory, Alfurate University. The results of the difference in the grinding process showed that the LMF flour is smoothly and brightly white and passed through the 280 mµ sieve holes compared to the MMF flour that passed through the sieve holes (265) mµ, as well as when estimating the average protein ratio, there was a Statistical significance difference between the tested samples that raised in MMF Also, an increase in the starch damage ratio in the flour of lab. mill LMF sample, the height of time and the absorbing iodine ratio compared to the floure of man. mill MMF flour sample. In addition it is noticed that a rise in the development time of the dough C1 with a Statistical significance and reached (1.2 and 2.9) minutes for MMF and LMF samples, respectively, as well as the MMF sample was distinguished by the high time of the dough stability and the fall number and with a Statistical significance, and no differences between the samples regarding the average of the torques of all stages of Mixolab, and the long of shelf life of baking bread from the flour of MMf, but there was a Statistical significance correlation relationship between some measures such as the percentage of protein, the value of the falling number and the dough stability. LMF can be directed to the manufacture of biscuits, and the MMF sample is suitable for noodles